Crystallization of [Zn(Pyrazinamide)₂(Cl)₂] Complex and In Vitro Antibacterial Activity of the Complex Against E. coli and S. aureus - Naila Azmi Adiba; Danar Purwonugroho; Arie Srihardyastutie; Yuniar Ponco Prananto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
A complex of [Zn(pza)2(Cl)2], pza = pyrazinamide, was successfully crystallized from methanol or ethanol solvents with different morphology. The complex was synthesized using the solution method in ZnCl2: pza mol ratios of 1:2 and 1:4 in both ethanol and methanol solvents. FTIR and single crystal XRD analyses were done to confirm the complex. The complex was then used for in vitro antibacterial test against E. coli and S. aureus. Experimental data shows that the type of solvent and metal-to-ligand mol ratio yields the same compound, resulting in colorless crystals that melt at 234-236°C. Large block crystals were obtained from the methanolic solution, while a higher yield was obtained from the use of a higher mol ratio of 1:4. Infrared spectra analysis confirms the presence of characteristic carbonyl and amide groups of the pza ligand. Meanwhile, single crystal XRD screening indicates that unit cell parameters of the crystals from both solvents are identical to a known zinc(II)-pza complex. In vitro antibacterial tests against E. coli and S. aureus show that the complex had much better activity than the ZnCl2 and the free pza. In addition, the complex performs better antibacterial activity toward gram-positive S. aureus than the gram-negative E. coli.